(untitled) (Research, Society and Development, 2021)
Education is related to other areas of knowledge, as well as neuroscience. Through the discovery of this and brain or neural plasticity, the complexity of learning at a biological level can be revealed, as well as helping the development of new methodologies and forms of learning. In this context, the study aimed to analyze the relationships between brain plasticity and learning, having neuroscience as a starting point. To this end, a bibliographic research was used, carried out in a virtual and material medium, in which the results were scored and the dialogues between the sources were scored, which were expressed in two topics in results and discussion. The author’s conclusions and impressions are in the final considerations.